Polarization behavior in the two stage sintered lead titanate ceramics - R. Wongmaneerung (2018)
Polarization behavior in lead titanate, prepared by the two stage sintering approach, is determined by using the dilatometer thermal expansion data. We report the temperature-dependent measurements of the strain, the magnitude of polarization, PS2, deduced from the sets of data gathered from the thermal expansion values. The calculated values of the electric polarization, PS, on the two stage sintered lead titanate ceramics show the simple approach to determine the temperature dependence of the polarization below and around the transition temperature. Various aspects of our understanding of the polarization behavior and other effects in the ferroelectric are discussed.